GERAKAN PENGENDALIAN ORGANISME PENGGANGGU TUMBUHAN (GERDAL OPT) DI PEKON WAY SINDI, KECAMATAN KARYA PENGGAWA - Sulistyono, Mahasiswa KKN Univeristas Lampung (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The need for food for the community is directly proportional to the increase in population, one of the food needs is rice which is the result of rice processing. Efforts to meet the increasing demand for rice must be balanced with an increase in rice production, both rice fields and fields. However, the expected rice production is sometimes not as expected due to crop failure due to attacks by plant-disturbing organisms (OPT). The steps that must be taken to control the pest through empowering farmers are carrying out a rice pest control movement. The pest control movement in Pekon Way Sindi, Karya Penggawa District, Pesisir Barat Regency aims to increase farmers' understanding of the types of organisms disturbing rice plants, increase understanding farmers how to control the attack of pest organisms in paddy rice plants and increasing farmers' understanding of Integrated Pest Management (IPM). This article is limited to the implementation of Pekon Way Sindi KKN Period 1 2023. This article also contributes to agricultural science as well as practices and strategies for implementing SDGs points.